2011
DOI: 10.1002/jcb.23056
|View full text |Cite
|
Sign up to set email alerts
|

The role of mechanical stretching in the activation and localization of adhesion proteins and related intracellular molecules

Abstract: The molecular complexity of the processes which lead to cell adhesion includes membrane and cytoskeletal proteins, involved in the focal adhesion formation, as well as signaling molecules tightly associated with the main intracellular regulatory cascades (Akt/PKB and MAPK/Erk). Dynamic environments, which create substrate deformations at determined frequencies and timing, have significant influences on adhesion mechanisms and in general in cellular behavior. In this work, we investigated the role of mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…Transmitted via intracellular signaling cascades including MAPK26, PI3K/Akt27, GTPases28, Wnt29 and calcium30 pathways, the signals modulate osteoblastic differentiation by up-regulation of genes such as Runx2, Alp , and Ocn 31. RUNX2 is a master control transcription factor of osteoblastic differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Transmitted via intracellular signaling cascades including MAPK26, PI3K/Akt27, GTPases28, Wnt29 and calcium30 pathways, the signals modulate osteoblastic differentiation by up-regulation of genes such as Runx2, Alp , and Ocn 31. RUNX2 is a master control transcription factor of osteoblastic differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation at different sites within FAK is catalyzed in distinct ways and affects various cellular functions. Previous studies regarding the FAK activation state in a variety of non-chondrocytic cell types under mechanical stress have mainly concentrated on the autophosphorylation site [25,26,27]. In a study on fibroblasts, Tyr 576/577 residues of FAK were shown to be required for the mechanical stress-induced cellular response [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition its ability to sense external forces, vinculin has been reported to regulate how applied mechanical stress alters adhesion composition in order to induce cell morphological changes. [37][38][39] Recent evidence indicates that vinculin is crucial for transmission of mechanical forces resulting from either actomyosin or cell-generated forces, since the recruitment of vinculin to FAs corresponds to the amount of force applied to the extracellular matrix (ECM). 40,41 Furthermore, the F-actin/vinculin interaction may be required for these forces since, without Vt, vinculin does not follow the retrograde flow of actin.…”
Section: -36mentioning
confidence: 99%